Smart Tourism Concepts to be applied for the Lake Toba Tourism Area - Posma Sariguna Johnson Kennedy (International Journal of Artificial Intelligence Research, 2022)
One way to improve tourism is to take advantage of information and communication technology advances. Smart Tourism is a tourism development that focuses on the application of Information and Communication Technologies (ICT) in an integrated manner with tourism programs. The purpose of the research is to study the concepts of smart tourism and how to apply them to the tourist area of Lake Toba, North Sumatra. The research method used in this study is a qualitative approach. The study on the concept of Smart Tourism was conducted using a literature review and discussion with several related resource persons. The city/district government in the Lake Toba tourist area of North Sumatra is now innovating to develop every tourism potential, both in terms of infrastructure development to smart branding as one of the smart tourism programs in promoting tourist destinations.